Initial orientation of the fretting fatigue cracks in shrink-fit connection specimens - Ciro Santus (Fracture and Structural Integrity)
The bending configuration of shrink-fitted connection fretting fatigue tests causes a fluctuation in the contact pressure and in turn a more favourable condition for shear, rather than tensile, crack initiation. According to the classification type I (shear) and type II (tensile) fretting cracks, type II was only observed in the tests with no surface enhancement, which experienced the lowest fretting strength and thus a reduced pressure fluctuation effect. The crack initial direction was predicted as the critical plane orientation undergoing the maximum Fatemi-Socie (FS) stress parameter, for the shallow type I shear cracks. A significant result is that if the critical plane is searched at the fretting hot-spot, an incorrect outward direction is obtained, since the orthogonal direction, with the same shear stress amplitude, experiences a more compressive maximum normal stress. Conversely, with the application of the Point Method, taking the stress location at half the critical distance and by following the potential critical plane, a higher shear stress along the inward direction is obtained. The more compressive stress below the contact can therefore be compensated, and consequently the inward shallow direction is correctly predicted.